Father involvement as a predictor of early childhood external behaviors in Indonesian - Nafisah, Aisyah Durrotun; Sugiyo Pranoto, Yuli Kurniawati; Nuzulia, Siti; Mulawarman, Mulawarman; Suminar, Tri (Intelektual Pustaka Media Utama, 2025)
The prevailing patriarchal culture in Indonesia that posits a father only to act as a breadwinner is thought to be the reason for the lack of father involvement in parenting. Therefore, this study aims to analyze father involvement in problematic behavior in children aged 3-4 years by considering the variables of father's socioeconomic status (SES) and child's gender. This study employs a quantitative descriptive approach through a multiple regression model coupled with survey. The selection of respondents was determined through quota sampling technique by considering the ease of access to data collection. With or without control over the SES of fathers and the gender of children, the engagement indicator contributes an impact to the problematic behavior in children, while accessibility does not. The problematic behavior in children is lower with the control over SES of fathers and the gender of children compared to the condition without control over these two variables. Of the two variables, only the father’s age indicator affects the problematic behavior in children. The results of this study can encourage fathers to get actively involved in raising their children in a way that is appropriate to the current cultural context and situation.